PENGARUH UMUR PERUSAHAAN, PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN - SOFIA PRIMA DEWI; KENI KENI (Jurnal Bisnis dan Akuntansi, 2013)
This study aimed to examine the effect of firm age, profitability, firm size and leverage on the disclosure of corporate Social responsibility. The sample used is the data 105 companies listed in Indonesia Stock Exchange during the years 2009-2011. Data analysis was performed with the help of the program PASW Statistics version 18.00. The results showed that the profitability and firm size has an influence on corporate social responsibility disclosure while firm age and leverage has no effect on the disclosure of corporate social responsibility.